The Types of Monochrome Glazed Ceramics in the Beçin Castle Excavation (2014-2021) - Tuğba Diri Apaydın (Sanat Tarihi Yıllığı)
Beçin is a residential center in the Milas District of the Turkish Province of Mugla in the Aegean Region. Becin has a history dating back to 2000 B.C. and is an important Anatolian city that has hosted many cultures such as the Carians in ancient times and the Mentese Principality in the Ottoman period. The main subject of this study involves the Turkish red monochrome-glazed clay ceramics and their types found in Beçin Castle excavations between 2014 and 2021. The technique of monochrome glazing is one of the most common decorating techniques applied in Byzantine, Principalities, and early Ottoman art. It was frequently encountered on the ceramics unearthed in the Beçin Excavation because of its ease of application and functionality. Ceramics such as bowls, plates, jugs, and oil lamps made using this technique were recovered mostly in pieces and sometimes whole in the excavations. Although green glaze is mostly seen in monochrome glaze ceramics, yellow and blue glazing were also frequently preferred. The inner surfaces of these ceramics are completely glazed, while the outside is only partially glazed. Monochrome glazed ceramics are grouped under their various forms. In the academic sources, especially bowls are classified as spherical, hemispherical, conical body or semi-conical body. The first aim of the study is to try to create a common typology by comparing the form features of the Medieval ceramics in the ceramic production centers in the east and west of Anatolia with the Beçin Castle ceramics. In addition, revealing the importance of Beçin ceramics in medieval Anatolia is among other purposes.